REGIONAL SMES IMPACT ON THE SUPPLY CHAIN MANAGEMENT OF THE GLOBAL ECONOMY - Lozitskaya, Olga; Ablaev, Ildar; Budko, Evgenia (International Journal of Supply Chain Management, 2020)
Abstract? Today, supply chain management has emerged as an important capability of operational excellence for companies. On the one hand, small and medium-sized businesses are managed by business families, and through this, owners will make strategic decisions to control and manage operations. Towards the growth of professionalization levels is risk-taking, which has a significant impact on business. Based on the results obtained, the main trends of the modern development of global family policy are highlighted, including the degree of its impact on the economic stability and the competitiveness of the country. The research is based on four macro-regions of the world: Europe, America, Asia, as well as Australia and New Zealand. The purpose of this paper is to provide a model for the relationship between the characteristics of small and medium-sized family businesses and supply chain management. The relevant model shows which of the family business requirements and supply chain management is effective. As a result, it was concluded that the strongest relationship between the family policy and economic development can be traced in supply chain management of Russia. Other regions of the world demonstrated a lower correlation. This emphasizes the non-synchronous impact of the decisions made by the state in the interests of the family on its global competitiveness. It was revealed that the improvement of economic indicators stimulates fertility in Russia, while in other countries, on the contrary, it provokes its decline.